Relações entre a ictiofauna e macrófitas aquáticas em lagoas do rio Pandeiros, Minas Gerais - Souza, Marcela Alves de (2016)
This work aimed to perform the sampling of the ichthyofauna associated to aquatic macrophytes in lakes of the Pandeiros River, Minas Gerais. The lakes were sampled in rainy and dry seasons in order to assess the relationship among the fish communities and the different compositions of macrophyte banks and also to compare the fish assemblies associated to macrophytes in the lake affected by the reservoir with downstream floodplains lakes, in Pandeiros River. In total 2,744 specimens of fishes belonging to 30 species were captured in the macrophyte banks. A total of 459 individuals and nine species were recorded in the reservoir lake, and 2,285 specimens and 30 species in the floodplain lakes. A total higher richness species of fishes was observed in the group formed by the three types of macrophytes (SEF). Differences were observed in the species composition of fishes among the different compositions of macrophyte banks, submerged (S), emergent+floating (EF), submerged+emergent (SE), submerged+emergent+floating (SEF), as well as in the community structure of these species. The composition of fish species also showed a complete distinction among the floodplain lakes and the lake affected by the reservoir. Four species of macrophytes were sampled in the reservoir lake and nine species in the floodplain lakes. There was a difference in the richness and abundance of fishes between sampling sites, with higher values for the floodplain. The average depth ranged from 66.5 cm in the dry season to 70 cm in the rainy season in the reservoir lake. In the floodplain lakes the difference was from 80 cm in the dry season to 120 cm in the rainy season. Results show a high capture of species as well as fish individuals associated to aquatic plants. This reinforces the premise that macrophytes present important ecological functions in lentic aquatic ecosystems such as flood plains.